2016
DOI: 10.1123/ijsnem.2015-0245
|View full text |Cite
|
Sign up to set email alerts
|

Female Recreational Exercisers at Risk for Low Energy Availability

Abstract: Low energy availability (LEA) describes the disruption in normal physiological function existent when insufficient energy intake is combined with exercise. To conserve energy a range of endocrine adaptations occur, impairing health and athletic performance. The prevalence of LEA has not been fully established especially among recreational exercisers. Determining recreational exercisers at risk of LEA may help to maximize prevention, early diagnosis and treatment. The design of this study was a cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 0 publications
5
46
3
Order By: Relevance
“…The current study’s findings are in line with the first study of prevalence for low EA in female recreational athletes, conducted by Slater et al [23]. These investigators found that 45.0% ( n = 49) of participants were categorized as being at risk of low EA.…”
Section: Discussionsupporting
confidence: 91%
“…The current study’s findings are in line with the first study of prevalence for low EA in female recreational athletes, conducted by Slater et al [23]. These investigators found that 45.0% ( n = 49) of participants were categorized as being at risk of low EA.…”
Section: Discussionsupporting
confidence: 91%
“…The overall sports nutrition knowledge scores were low, with the lowest level of knowledge related to supplementation (18% correctly answered). Furthermore, 30% of players were deemed to be at risk of LEA, which is similar to previously reported rates in female athletes [19,20].…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, there is currently no gold standard approach for the measurement of exercise energy expenditure, as many tools used in an applied context, including accelerometers, underestimate energy expenditure at high exercise intensities [18]. Because of the challenges associated with directly measuring EA, the validated Low Energy Availability in Females Questionnaire (LEAF-Q) has been used to assess the risk of LEA in athletes, with the prevalence reported to range between 33 and 46% [19,20]. However, most of the existing literature has focused on endurance athletes, and little is known about team sport athletes.…”
Section: Introductionmentioning
confidence: 99%
“…On the first day of pre-season training (November 2014), participants completed a 49item questionnaire on body image and disordered eating behaviours. The questionnaire was developed from the Low Energy Availability Amongst New Zealand Athletes (LEANZ) questionnaire, (Slater, McLay-Cooke, Brown, & Black, 2016) which sourced questions from the Low Energy Availability in Female Athletes Questionnaire, and the Eating Disorder Inventory-3 (EDI-3) questionnaire, described elsewhere (Garner, 2004;Melin et al, 2014;Slater et al, 2016). Some questions were further modified to suit the participants in the current study.…”
Section: Body Image and Eating Behaviour Questionnairementioning
confidence: 99%